Affixation in Javanese Language Uttered by Sumber Agung Villagers - Magria, Vera; Sari, Yunita (Krinok:Jurnal Linguistik Budaya, 2023)
This research studies about affixes. The purposes of this research to identify the kinds of affixes, the process and the function of affixation in Javanese Language uttered by Sumber Agung villagers. This research uses descriptive qualitative method. Data are gained through participating technique, recording technique, and writing technique. The data are analyzed with theories proposed by Yule (1985) and Connor-Linton (2006). The data are presented through informal method.The results of this research show that there are 65 words of Javanese Language which are embedded with affixes. There are 4 kinds of affixes; prefixes, suffixes, infixes, and confixes. The five kinds of prefixes include {ng-}, {di-}, {ben-}, {ke-}, and {ny-}. The five kinds of suffixes include {-e}, {-ne}, {-an}, {-ane}, and {-en}, 1 word is involved in one kind of infix that is {-cici-}, and 5 words are involved in 2 kinds of confixes. The two confixes include {di--i} and {ng--i}. The process of affixes of this research includes derivational and inflectional affixation. The affixes have function of forming noun, verb, adjective, adverb, and numeric